Local Wisdom in the Cultural Symbol of Indonesian Traditional House - Sopa, M (KnE Social Sciences, 2018)
The research aims to reveal the local wisdom through the cultural symbol in Indonesian Traditional House particularly Umah Edet Pitu Ruang Gayo. This research used a qualitative method with an ethnographic approach. The source of data were conducted through documentation study, observation, and interviews. The research Revealed that the design of Umah Pitu Ruang are divided into two parts, they are basic structural design and motif of kerrawang Gayo. The results of the research revealed that based on design, there are 4 symbols namely Gergel symbolizes “unity”, Luangi ni puting suyen symbolizes ”blessing”, Bubung urum Rongka symbolizes “protection”. and Benang serta peceng symbolizes the right of ulama, in other words the priest or ulama is obliged to correct the wrong. Based on motif, there are 13 symbols namely emun beriring, emun mutumpuk, emun berkune, emun mupesir, emun berangkat, puter tali, Pucuk rebung, sarak opat and lelayang. Based on color there are 5 symbols, including yellow, green, red, white, and black. Keywords: Traditional House, Local Wisdom, Cultural Symbol